Instruments in the classroom - Berkow, Peter; Berkow, Anita; Speer, Robert; Magna Systems, Inc. (Lake Zurich, Ill. : Magna Systems Inc., 2007)
Musical instruments work well in the classroom. This program demonstrates the use of musical instruments in pre-school and kingdergarden classrooms. A wide variety of ideas are presented to help incorporate musical instruments into a curriculum
Title from title screen
Program 3: Instruments
Executive producer, Alissa English, Joe Lombardo ; edited by Tyler Bingham ; cameras, Anita Berlow, Dan Carter, Peter Berkow
Narrator: Alice Burkhart-Roberts
Keywords: Musical instruments -- Methods -- Group instruction; Musical instruments